Effects of linsitinib on M22 and IGF:1-treated 3D spheroids of human orbital fibroblasts - Fumihito Hikage; Megumi Suzuki; Tatsuya Sato; Araya Umetsu; Toshifumi Ogawa; Nami Nishikiori; Masato Furuhashi; Hiroshi Ohguro; Megumi Watanabe (Scientific Reports)
Abstract To elucidate the role of IGF1R inhibition in the pathogenesis of Graves’ orbitopathy (GO), the effects of linsitinib (Lins) on a recombinant human TSHR antibody (M22) and IGF1 to activate TSHR and IGF1R of human orbital fibroblasts (HOFs) obtained from patients without GO (HOFs) and patients with GO (GHOFs) were studied using in vitro three-dimensional (3D) spheroid models in addition to their 2D planar cell culture. For this purpose, we evaluated 1) cellular metabolic functions by using a seahorse bioanalyzer (2D), 2) physical properties including size and stiffness of 3D spheroids, and mRNA expression of several extracellular matrix (ECM) proteins, their modulators (CCL2 LOX, CTGF, MMPs), ACTA2 and inflammatory cytokines (IL1β, IL6). Administration of IGF1 and M22 induced increases of cellular metabolic functions with the effect on HOFs being much more potent than the effect on GHOFs, suggesting that IGF1R and TSHR of GHOFs may already be stimulated. Lins had effects similar to those of IGF1/M22 on cellular biological functions of HOFs but not on those of GHOFs. As for physical properties of 3D GHOFs spheroids, stiffness but not size was significantly increased by IGF1 and/or M22. In contrast, Lins significantly inhibited the M22-induced increase in stiffness despite the fact that Lins alone had no effect. The mRNA expression levels of several genes of ECM proteins and most of the other genes also fluctuated similarly to the changes in stiffness of 3D spheroids despite the fact that Lins induced up-regulation of inflammatory cytokines and MMP3. The findings presented herein indicate that IGF1R inhibition by Lins may beneficially affect GO-related fibrogenesis.